Z-Type Employees and Tenure as Mediators Between Traditional Management Behaviour and Job Satisfaction - ŞAHİN ÖREN, Tuba and ÖREN, Veli Erdinç (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study investigates the mediating roles of Generation Z employees and ten-ure in the relationship between traditional management behavior and job satisfaction within the hospitality industry. As Generation Z increasingly enters the workforce, partic-ularly in the hotel sector, their expectations -such as participative leadership, work-life balance, and meaningful work - often clash with traditional managerial approaches characterized by hierarchical structures, limited employee involvement, and centralized decision-making. Based on a cross-sectional survey of 612 hotel employees from Generation Z in Türkiye, data were analyzed using Hayes’ PROCESS macro (Model 6) for serial mediation. The results reveal that traditional management behavior negatively affects Generation Z employees and indirectly reduces their job satisfaction through shortened tenure. Furthermore, the serial mediation model confirms that Generation Z and tenure significantly mediate the impact of traditional management behavior on job satisfaction. These findings underscore the importance of adapting management styles to generational needs and tenure dynamics in order to enhance employee well-being and organizational performance. The study contributes to organizational behavior literature by integrating generational theory and social exchange theory to explain job satisfaction in a generation-ally diverse workplace.